Retraction Note: RNAi targeting CXCR4 inhibits proliferation and invasion of esophageal carcinoma cells - Tao Wang; Yanfang Mi; Linping Pian; Ping Gao; Hong Xu; Yuling Zheng; Xiaoyan Xuan (BMC, 2019)
The Editor-in-Chief has retracted this article [1] because Fig. 3 shows overlap with Fig. 6 in [2], Fig. 2b in [3] and Fig. 6a in [4]. An investigation by Zhengzhou University has confirmed that these figures overlap. The data reported in this article are therefore unreliable.